Presenting the Model of Health Technomarts with the Approach of Marketing Knowledge-Based Products: Grounded Theory - Solmaz Sadat Naghavi Alhosseini; Naser Azad; Changiz Valmohammadi; Abdollah Naami (Health Technology Assessment in Action)
Background: Knowledge-based companies often prioritize the scientific and technical aspects of their products, while marketing considerations receive less attention. However, to achieve a competitive advantage, it is essential to address both technological and marketing dimensions. Fan markets emerge as valuable tools to facilitate technology development activities and strengthen the technology market. Objectives: The present study aimed to provide a model for the health technomart with the approach of marketing knowledge-based products. Methods: This research is qualitative and was conducted using the grounded theory method with the Glaser approach. Data were collected through semi-structured interviews with 10 purposefully selected health experts. Data analysis was performed in three stages: Open, selective, and theoretical coding, using MAXQDA version 2020 software. Results: Data analysis resulted in the extraction of 156 open codes, 21 sub-categories, and 7 main categories. The results indicated that management of technology development and transfer, technology development infrastructures, technology policy, technology market management, technological product development, institutional factors related to technology development, and improving the technological business environment are the main categories of health technomart with the approach of marketing knowledge-based products. Conclusions: The presented model can help improve the performance of technomarts and the marketing and sales of knowledge-based and technology-oriented products in the health field.